Dexmedetomidine prolongs levobupivacaine analgesia via inhibition of inflammation and p38 MAPK phosphorylation in rat dorsal root ganglion. (11th October 2017) - Yamakita, Shunsuke; Matsuda, Megumi; Yamaguchi, Yosuke; Sawa, Teiji; Amaya, Fumimasa
Highlights: Peripheral dexmedetomidine prolongs reginal analgesia by the levobupivacaine in rat plantar incision model. Levobupivacaine with dexmedetomidine inhibited p38 MAPK phosphorylation in DRG neurons after the incision. Levobupivacaine and dexmedetomidine reduced macrophage accumulation and TNF-α synthesis in the plantar tissue. p38MAPK is responsive for the adjunctive analgesic effect of dexmedetomidine on the local anesthetics. Abstract: Following tissue injury, phosphorylation of p38 MAPK in the primary afferent neurons drives sensitization of peripheral nerve. Dexmedetomidine extends the duration of reginal analgesia by local anesthetics. The effect of regional analgesia on the peripheral nerve sensitization is not known. The aim of this study is to investigate the effect of regional analgesia by levobupivacaine with or without dexmedetomidine on the p38 MAPK phosphorylation in the dorsal root ganglion (DRG) and inflammatory reaction in the peripheral tissue. A plantar incision was made in the hind paws of Sprague–Dawley rats. Prior to incision, levobupivacaine with or without dexmedetomidine was injected to the plantar aspect of the paws and ankles. A behavioral study was performed to investigate pain hypersensitivity. Phosphorylation of p38 MAPK in the DRG was assessed by immunohistochemistry and Western blotting. Macrophage accumulation, NGF, and TNF-α in the DRG and plantar tissue were measured using immunohistochemistry, real-time PCR and ELISA. Pain hypersensitivity was induced immediately after the plantar incision. Treatment with levobupivacaine inhibited the development of pain hypersensitivity for two hours. Adjunctive dexmedetomidine extended the anti-hyperalgesic duration for four hours. Levobupivacaine without dexmedetomidine could not inhibit p38 MAPK phosphorylation in the DRG completely. However, Levobupivacaine and dexmedetomidine completely inhibited p38 MAPK phosphorylation, and reduced macrophage accumulation and TNF-α amount in the plantar tissue. Inhibition of p38 MAPK phosphorylation via TNF-α suggests dexmedetomidine has a peripheral mechanism of anti-inflammatory action when used as an adjunct to local anesthetics, and provides a molecular basis for the prevention of peripheral sensitization following surgery.